2005
DOI: 10.1021/bm049461t
|View full text |Cite
|
Sign up to set email alerts
|

Role of Water in Structural Changes of Poly(AVGVP) and Poly(GVGVP) Studied by FTIR and Raman Spectroscopy and ab Initio Calculations

Abstract: Two elastin-like poly(pentapeptides), poly(AV1GV2P) and poly(G1V1G2V2P), have been studied in water and in solid state by ATR FTIR and Raman spectroscopy in combination with model ab initio calculations. In aqueous solutions below the transition temperature T(t), a part of the amide groups and of the methyl groups of both polypentapeptides interacts with neighboring water molecules, whereas the other part of amide groups mutually interacts forming a beta-sheetlike structure. Below T(t), poly(AV1GV2P) is dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 20 publications
6
94
0
2
Order By: Relevance
“…3, FTIR spectra of elastin hydrogel showed two main peaks at 1535 cm À1 , and 1655 cm À1 corresponding to the amide II and amide I bands, respectively. Similar peaks were observed for bovine elastin and k-elastin [25], human elastin [26], bovine tropoelastin [27], a-elastin [28,29], two elastinlike poly(pentapeptides) [30], and synthetic elastin hydrogels [31]. The FTIR spectra of PCL showed a main peak at 1725 cm À1 attributed to C]O stretching; this peak was also observed in previous studies for electrospun PCL samples [32].…”
Section: Ftir Analysis On Compositessupporting
confidence: 84%
“…3, FTIR spectra of elastin hydrogel showed two main peaks at 1535 cm À1 , and 1655 cm À1 corresponding to the amide II and amide I bands, respectively. Similar peaks were observed for bovine elastin and k-elastin [25], human elastin [26], bovine tropoelastin [27], a-elastin [28,29], two elastinlike poly(pentapeptides) [30], and synthetic elastin hydrogels [31]. The FTIR spectra of PCL showed a main peak at 1725 cm À1 attributed to C]O stretching; this peak was also observed in previous studies for electrospun PCL samples [32].…”
Section: Ftir Analysis On Compositessupporting
confidence: 84%
“…The CH 3 stretching and bending modes are sensitive to the local changes in the surrounding medium of polymer chains and observed frequency shifts are related to the changes in the intermolecular arrangement of water molecules. In previous studies of polypentapeptides in water solutions, the observed increase of the asymmetric stretching frequency of the CH 3 groups sitting on the valine residues was correlated with increasing number of water molecules surrounding these groups [45,46]. The model structure shown in Fig.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 85%
“…The coil-globule transition of PNIPAM and PNIPMAM has received interest because these polymers exhibit the transition temperatures in aqueous solutions near room temperature. An analogous behavior was investigated on a large set of polymers within the elastin-like family [25][26][27][28][29]. All these materials show enormous potential for use in different technological fields and biomedicine, and therefore, understanding of their structural changes is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…The pair of polymers PNIPAM and PNIPMAM with amide groups in side chains, is analogous to poly(GVGVP) and poly(AVGVP), elastin-like poly(pentapeptides) with amide groups in the main chains differing by the presence of a methyl group in the residue lying between proline (P) and valine (V), glycine (G) or alanine (A). In a recent study of poly(GVGVP) and poly(AVGVP) by ATR FTIR and Raman spectroscopy in combination with quantum chemical calculations was found [29] that below T t only a part of amide groups and of methyl groups of both poly(pentapeptides) interact with the neighboring water molecules, while the second a strong effect on the physical structure of water solutions. Although the hydrophobic interactions for PNIPMAM and PNIPAM are very similar, PNIPMAM with additional methyl group exhibits significantly weaker intermolecular interactions between the amide groups.…”
Section: Introductionmentioning
confidence: 99%